KEMAMPUAN KOMUNIKASI PESERTA DIDIK TERHADAP PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION - Siregar, Rika Arnita; Eliza, Rivdya; Sepriyanti, Nana (Math Educa Journal, 2024)
This study was motivated by the low mathematical communication skills of students in class VIII MTsN Padang Panjang City. The purpose of this study was to determine the mathematical communication skills of students who learn with the Realistic Mathematics Education (RME) approach. This research is an experimental research with randomized control group only design. The population in this study were all students of class VIII MTsN Kota Padang Panjang, after testing normality, homogeneity and equality of means and the results were significant, then sampling was carried out by drawing, so that VIII-E was obtained as the control class and VIII-G as the experimental class. The instrument used was a mathematical communication ability test. The data analysis technique used was one-way t-test. Based on the results of hypothesis testing with t-test, obtained ttable = 1.67 and tcount = 2.42 so that tcount ttable then H0 is rejected and H1 is accepted. It can be concluded that students' mathematical communication skills are higher when learning by using the Realistic Mathematics Education approach than students who learn by using a scientific approach in class VIII MTsN Kota Padang Panjang.